1999
DOI: 10.1002/(sici)1097-0290(19990105)62:1<71::aid-bit9>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dissolved oxygen and carbon dioxide concentration profiles in tubular photobioreactors for microalgal culture

Abstract: Abstract:A model is developed for prediction of axial concentration profiles of dissolved oxygen and carbon dioxide in tubular photobioreactors used for culturing microalgae. Experimental data are used to verify the model for continuous outdoor culture of Porphyridium cruentum grown in a 200-L reactor with 100-m long tubular solar receiver. The culture was carried out at a dilution rate of 0.05 h −1 applied only during a 10-h daylight period. The quasi-steady state biomass concentration achieved was 3.0 g и L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 0 publications
3
37
1
Order By: Relevance
“…Oxygen (O 2 ) is a product of photosynthesis and levels above atmospheric O 2 levels (0.2247 mol O 2 m -3 ) can inhibit photosynthesis in a number of microalgal species, even when the CO 2 levels remain elevated (Aiba, 1982). Furthermore, elevated levels of O 2 coupled with high irradiance can lead to photo-oxidation (Richmond, 1990;Camacho Rubio et al, 1999).…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 99%
“…Oxygen (O 2 ) is a product of photosynthesis and levels above atmospheric O 2 levels (0.2247 mol O 2 m -3 ) can inhibit photosynthesis in a number of microalgal species, even when the CO 2 levels remain elevated (Aiba, 1982). Furthermore, elevated levels of O 2 coupled with high irradiance can lead to photo-oxidation (Richmond, 1990;Camacho Rubio et al, 1999).…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 99%
“…Two studies demonstrated CO 2 utilization efficiencies around 70% without significant productivity penalties (Valiorgue et al 2014;Yang 2011). Other studies report CO 2 utilization efficiencies up to 95%, however, the implications for biomass productivity were not quantified (Doucha and Lívanský 2006;Rubio et al 1999). To perform these optimizations, a mathematical model specific for the cultivation system is required, therefore, this model is specific for the Algadisk reactor.…”
Section: Maximization Of Co 2 Utilization and Biomass Productivity Bymentioning
confidence: 99%
“…For microalgae grown in suspended cultures, processes with minimal CO 2 loss have been developed by employing experimentally validated models (Doucha and Lívanský 2006;Rubio et al 1999;Valiorgue et al 2014;Yang 2011). Their primary conclusion is that CO 2 utilization can be improved by increasing the mass transfer from the gas to the liquid (Doucha and Lívanský 2006;Rubio et al 1999;Valiorgue et al 2014;Yang 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on algal production rates for biofuels and commercial products has lead to a plethora of work on open bioreactors, such as ponds and raceway flumes [4,, and closed bioreactors, such as vertical , horizontal [34,40, and helical tubes [97,[143][144][145][146][147][148][149][150][151][152][153][154], flat plates [66,, and other unique designs [133,[185][186][187][188][189]. This research dates back to the early 1950s and was chronicled in a historical perspective by Borowitzka [190].…”
Section: Introductionmentioning
confidence: 99%